Análise da influência dos fatores naturais e antrópicos na disponibilidade hídrica no alto curso do Córrego Três Marcos: subsídios para gestão integrada das águas superficial e subterrânea - Oliveira, Hérica Leonel de Paula Ramos (2012)
The presence of water on our planet is crucial to the existence of the essential conditions for the origin and maintenance of life on its surface. This study sought to analyze the use and occupation and their influence on water availability in the upper course of the stream Três Marcos. The choice of the upper course of the stream Três Marcos was due to its importance as a source of water used for irrigation on small farms in the system of family farming. However, part of this area falls within the urban area of Uberlândia, which has shown a high growth rate of urban occupation in recent decades, resulting in severe impacts on water resources. The area studied is located in the eastern portion of the city of Uberlândia, occupying an area of 11,432,442.86 square meters, which is cut by highways BR-365, oriented in a northeast-southwest direction and by BR-452. The operational procedures and methods constituted on the use of cartographic documents from IBGE and IBC / GERCA, from USAF; literature researches; field surveys; streamflow measurement; water balance; survey of geological geomorphological and hydrogeological factors of the studied area; trials in situ to obtain the permeability coefficient (k) of the soil; mapping of the occupation and evolution of the use of soil; mapping the area of contribution. These mappings were developed in the software ArcGis 9.3. From the results obtained, it is observed that the soils analyzed have relative permeability and, due to their characteristics, mainly because of its association with residual unconsolidated materials of Marilia formation, can be considered of great performance for aquifer recharge. Most of the watershed area of contribution is very flat topography, characterized as recharge areas of local and regional aquifers. It is denoted from the information about the use and occupation of the soil that the studied area is intensely occupied, with a significant portion already urbanized / built, while the remaining area is divided between areas of short-cycle cultivation, grazing areas, watershed formed by pluvial infiltration, remnants of Cerrado, small farms and other. Furthermore, it concludes that the containment ponds and infiltration of pluvial water coming from the Morumbi neighborhood, which are established near the headwaters of the stream Três Marcos, do not received proper maintenance, as there is presence of solid waste within, and disruptions that have led to erosion. It is considered that the area where it was developed in the Morumbi neighborhood constitutes in the main recharge area of groundwater zone that feeds the headwaters of the stream Três Marcos, once its topography shows the characteristic form of mild depression, which allows accumulation of pluvial water and its infiltration. With the results of the research is expected to provide subsidy for better planning of the use of its waters for the development of economic activities as well as the provision of information to government and non-governmental agencies to propose a plan that comprehends the integrated assessment of surface water and groundwater in the studied area.